Anti-pollution composite nanofiber membrane for high-precision protein separation and preparation method of anti-pollution composite nanofiber membrane
By grafting zwitterionic brushes onto the surface of nanofiber membranes using electrospinning and surface-initiated atom transfer radical polymerization, the problem of easy fouling of polymer separation membranes is solved, achieving high-precision and high-throughput protein separation.
Patent Information
- Application Number
- CN202511897285.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-16
- Publication Date
- 2026-02-10
AI Technical Summary
Existing polymer separation membranes are prone to membrane fouling during protein separation, leading to flux decline and reduced accuracy, and modification methods suffer from insufficient stability.
Hydrophilic polymer/zwitterionic polymer blended nanofiber substrate film was prepared by electrospinning technology, and zwitterionic brushes were grafted onto the fiber surface by surface-initiated atom transfer radical polymerization (SI-ATRP) technology to form a stable highly hydrated layer.
It achieves high-precision, high-throughput protein separation with BSA rejection rate >99% and throughput recovery rate >90%, and the modified layer has good stability and is not easy to fall off.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of advanced separation functional material preparation, and particularly relates to an anti-fouling nanofiber composite membrane for separation of biological macromolecules and a preparation method thereof. BACKGROUND
[0002] At present, efficient separation and purification technology of proteins has a wide and urgent demand in the fields of biopharmaceuticals, clinical diagnosis, food engineering and life science research. Membrane separation technology has become an important means for protein separation because of its simple operation, low energy consumption and easy scaling up. However, traditional polymer separation membranes, such as polyether sulfone (PES) and polyacrylonitrile (PAN) ultrafiltration / microfiltration membranes, still face severe challenges in practical applications. These membrane materials are inherently hydrophobic, and when processing biological macromolecules such as proteins, membrane fouling occurs easily. Proteins are adsorbed on the membrane surface and in the pores through non-specific interactions such as hydrophobic interaction and electrostatic interaction, causing membrane pore blockage, reduction of effective filtration area, and thus leading to rapid attenuation of separation flux, increase of operating pressure, and decrease of separation precision. Frequent membrane fouling not only significantly increases the cost of cleaning and regeneration and downtime, but also significantly shortens the service life of the membrane, becoming a key bottleneck restricting the improvement of separation efficiency and economic benefits.
[0003] To improve the anti-fouling performance of the membrane, common modification strategies include polyethylene glycol (PEG) grafting and surface coating of a hydrophilic layer. PEG has been widely used due to its good hydration capacity, but its molecular chain is easily oxidized and degraded under long-term operation or in the presence of oxidizing agents, leading to gradual loss of anti-fouling performance. Physical coating methods have the problem of weak adhesion between the coating and the base membrane, and the coating is prone to fall off, which lacks stability and durability, and the modification effect is difficult to maintain in long-term industrial operation.
[0004] In recent years, zwitterionic materials such as polysulfobetaine (PSBMA) and polycarboxybetaine (PCBMA) have attracted widespread attention due to their unique molecular structure. This type of material can combine a large number of water molecules through strong electric dipole interaction, forming a dense and stable "hydration layer" on the membrane surface, which can effectively block the direct contact of proteins with the membrane surface, thus exhibiting super strong anti-fouling properties close to "zero adsorption", and being hailed as a new generation of "ultimate" anti-fouling material. Although the concept of zwitterionic modification is advanced, most existing technologies still use traditional phase inversion membranes as the base material. Such base membranes have inherent limitations: relatively low specific surface area, asymmetric sponge-like pore structure, and wide pore size distribution. Surface modification based on this, grafting or coating, can easily reduce or even block the effective pore size of the membrane, often sacrificing the permeation flux of the membrane while obtaining anti-fouling properties, making it difficult to achieve the synergistic improvement of high flux and high selectivity separation.
[0005] Therefore, developing a novel separation membrane that can fundamentally solve the problem of protein contamination while maintaining high throughput, high precision, and long-term operational stability has become an important and highly challenging topic in the field of membrane science. This development not only has significant scientific research value but also has significant practical implications for promoting the industrial upgrading of bioseparation engineering. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a protein separation membrane that is simple to prepare, has excellent anti-fouling performance, high separation throughput and is stable.
[0007] A method for preparing an antifouling composite nanofiber membrane for protein separation, comprising the following specific steps: (1) Preparation of spinning solution: The spinning solution is prepared by the following components according to the mass percentage, wherein the hydrophilic polymer is 70-95%, the zwitterionic polymer is 5-30%, the total solid content is 10-25 wt%, and the remainder is organic solvent; the hydrophilic polymer and the zwitterionic polymer are dissolved in the organic solvent according to the mass percentage, heated and stirred at 60°C for 12-24 h until a transparent casting solution is formed, and then allowed to stand to remove bubbles; (2) Electrospinning: The spinning solution is spun under the conditions of voltage 16-18 kV, feed rate 0.8-1.4 mL / h, and receiving distance 10-16 cm to obtain nanofiber base film; (3) Surface activation: The nanofiber substrate obtained in step (2) is immersed in a solution containing ATRP initiator and reacted at 25°C for 1-3 h to activate and modify the surface of the fiber membrane and introduce initiation sites; (4) Surface grafting polymerization: The activated membrane in step (3) is placed in a reaction system containing ligands and catalysts and reacted for 1-4 h to carry out surface-initiated atom transfer radical polymerization reaction, and zwitterionic polymers are grafted onto the surface of the nanofiber membrane; after the reaction is completed, the membrane is washed with pure water and dried at 30-45℃ to obtain the composite nanofiber membrane.
[0008] Preferably, the hydrophilic polymer in step 1) is polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyethersulfone (PES), or polyvinyl alcohol (PVA); the zwitterionic polymer is polysulfobetaine methacrylate (PSBMA) or polycarboxybetaine methacrylate (PCBMA).
[0009] Preferably, the organic solvent in step 1) is one of N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, or N-methylpyrrolidone.
[0010] Preferably, the ATRP initiator in step (3) is 2-bromoisobutyryl bromide (BiBB) or a trichlorosilane derivative initiator.
[0011] Preferably, the concentration of the ATRP initiator in step (3) is 0.1-0.3 mol / L.
[0012] Preferably, in step (4), the ligand is N, N, N', N'', N''-pentamethyldiethylenetriamine (PMDETA) or tris(2-pyridylmethyl)amine (TPMA), and the catalyst is CuCl or CuBr.
[0013] Preferably, the reaction system in step (4) is prepared by mass percentage of 50-70% ligand and 30-50% catalyst.
[0014] This invention provides an antifouling composite nanofiber membrane for high-precision protein separation and its preparation method. The membrane is characterized in that it separates a mixed solution of BSA and lysozyme with a BSA rejection rate >99% and a flux recovery rate >90%.
[0015] The core innovation of this invention lies in: Innovative Base Membrane: A hydrophilic polymer / zwitterionic polymer blend nanofiber base membrane was prepared using electrospinning technology. This base membrane possesses high porosity (>80%), three-dimensional interconnected channels, and excellent intrinsic antifouling potential, providing an ideal high specific surface area platform for subsequent modification.
[0016] Technological innovation in modification: Surface-initiated atom transfer radical polymerization (SI-ATRP) technology is used to achieve high-density, uniform, and covalent grafting of zwitterionic brushes onto the fiber surface, forming a stable and durable highly hydrated antifouling layer. This method results in high polymer chain density, strong bonding, and resistance to detachment, forming a durable and stable ultra-hydrating layer that fundamentally eliminates protein adsorption.
[0017] Synergistic effect: The high throughput of nanofiber-based membranes combined with the strong antifouling properties of zwitterionic brushes achieve a "1+1>2" effect, which significantly improves the efficiency and accuracy of protein separation in complex samples.
[0018] The anti-fouling composite nanofiber membrane prepared by this invention also has the advantages of high-precision and high-throughput protein separation and purification processes, and has broad application prospects in the fields of biomedicine and clean energy. Attached Figure Description
[0019] Figure 1 Image of the spinning solution in Example 1; Figure 2 The surface SEM image of the nanofiber-based membrane prepared in Example 2; Figure 3 SEM image of the surface of the composite nanofiber membrane prepared in Example 3; Figure 4 The image shows the surface SEM image of the composite nanofiber membrane prepared in Example 5. Detailed Implementation
[0020] The present invention will be further described below with reference to specific embodiments.
[0021] Example 1 A method for preparing an antifouling composite nanofiber membrane for protein separation, comprising the following specific steps: (1) Preparation of spinning solution: The spinning solution is prepared by the following components in the following mass percentages: PAN 70%, PSBMA 5%, total solid content 25 wt%, and the remainder is N,N-dimethylacetamide; PAN and PSBMA are dissolved in an organic solvent in the following mass percentages, heated and stirred at 60°C for 12 h until a transparent casting solution is formed, and then allowed to stand to remove bubbles; the image of the spinning solution is shown below. Figure 1 As shown.
[0022] (2) Electrospinning: The spinning solution was spun at a voltage of 16 kV, a feed rate of 0.8 mL / h, and a receiving distance of 10 cm to obtain a nanofiber base film; (3) Surface activation: The nanofiber substrate membrane obtained in step (2) is immersed in a solution containing 0.1 mol / L BiBB and reacted at 25°C for 1 h to activate and modify the surface of the fiber membrane and introduce initiation sites; (4) Surface grafting polymerization: The activated membrane from step (3) was placed in a reaction system composed of 50% PMDETA and 50% CuCl by mass percentage and reacted for 1 h to carry out surface-initiated atom transfer radical polymerization to graft zwitterionic polymers onto the surface of the nanofiber membrane. After the reaction was completed, the membrane was washed with pure water and dried at 30°C to obtain the composite nanofiber membrane. The highly hydrophilic composite membrane separated a mixed solution of BSA and lysozyme, with a BSA rejection rate >99.2% and a flux recovery rate >90%.
[0023] Example 2 A method for preparing an antifouling composite nanofiber membrane for protein separation, comprising the following specific steps: (1) Preparation of spinning solution: The spinning solution is prepared by the following components according to the mass percentage, of which PVDF 95%, PCBMA 30%, total solid content is 10 wt%, and the remainder is N,N-dimethylacetamide; PVDF and PCBMA are dissolved in an organic solvent according to the mass percentage, heated and stirred at 60℃ for 16 h to form a transparent casting solution, and then allowed to stand to remove bubbles; (2) Electrospinning: The spinning solution was spun under the conditions of 18 kV voltage, 1.4 mL / h feed rate, and 10 cm receiving distance to obtain a nanofiber substrate membrane; the surface SEM image of the prepared nanofiber substrate membrane is shown below. Figure 2 As shown.
[0024] (3) Surface activation: The nanofiber substrate obtained in step (2) is immersed in a solution containing 0.1 mol / L trichlorosilane derivative and reacted at 25°C for 3 h to activate and modify the surface of the fiber membrane and introduce initiation sites; (4) Surface grafting polymerization: The activated membrane from step (3) was placed in a reaction system composed of 70% TPMA and 30% CuBr by mass percentage and reacted for 4 h to carry out surface-initiated atom transfer radical polymerization to graft zwitterionic polymers onto the surface of the nanofiber membrane. After the reaction was completed, the membrane was washed with pure water and dried at 35°C to obtain the composite nanofiber membrane. The highly hydrophilic composite membrane separated a mixed solution of BSA and lysozyme, with a BSA rejection rate >99.5% and a flux recovery rate >93%.
[0025] Example 3 A method for preparing an antifouling composite nanofiber membrane for protein separation, comprising the following specific steps: (1) Preparation of spinning solution: The spinning solution is prepared by the following components according to the mass percentage, wherein PES 80%, PSBMA 20%, total solid content is 15 wt%, and the remainder is N,N-dimethylformamide; PES and PSBMA are dissolved in an organic solvent according to the mass percentage, heated and stirred at 60°C for 14 h until a transparent casting solution is formed, and then allowed to stand to remove bubbles; (2) Electrospinning: The spinning solution was spun at a voltage of 16 kV, a feed rate of 1.2 mL / h, and a receiving distance of 14 cm to obtain a nanofiber base film; (3) Surface activation: The nanofiber substrate membrane obtained in step (2) is immersed in a solution containing 0.3 mol / L BiBB and reacted at 25°C for 3 h to activate and modify the surface of the fiber membrane and introduce initiation sites; (4) Surface grafting polymerization: The activated membrane from step (3) was placed in a reaction system composed of 60% TPMA and 40% CuBr by mass percentage and reacted for 4 h to carry out surface-initiated atom transfer radical polymerization, grafting zwitterionic polymers onto the surface of the nanofiber membrane; after the reaction was completed, the membrane was washed with pure water and dried at 35°C to obtain the composite nanofiber membrane. The SEM image of the prepared composite nanofiber membrane is shown below. Figure 3 As shown. The highly hydrophilic composite membrane separates a mixed solution of BSA and lysozyme, with a BSA rejection rate >99.1% and a flux recovery rate >91%.
[0026] Example 4 A method for preparing an antifouling composite nanofiber membrane for protein separation, comprising the following specific steps: (1) Preparation of spinning solution: The spinning solution is prepared by the following components according to the mass percentage, wherein PVA 75%, PSBMA 25%, total solid content is 15 wt%, and the remainder is N-methylpyrrolidone; PVA and PSBMA are dissolved in organic solvent according to the mass percentage, heated and stirred at 60°C for 12 h until a transparent casting solution is formed, and then allowed to stand to remove bubbles; (2) Electrospinning: The spinning solution was spun at a voltage of 16 kV, a feed rate of 1.2 mL / h, and a receiving distance of 14 cm to obtain a nanofiber base film; (3) Surface activation: The nanofiber substrate obtained in step (2) is immersed in a solution containing 0.2 mol / L BiBB and reacted at 25°C for 1 h to activate and modify the surface of the fiber membrane and introduce initiation sites; (4) Surface grafting polymerization: The activated membrane from step (3) was placed in a reaction system composed of 60% TPMA and 40% CuBr by mass percentage and reacted for 4 h to carry out surface-initiated atom transfer radical polymerization to graft zwitterionic polymers onto the surface of the nanofiber membrane. After the reaction was completed, the membrane was washed with pure water and dried at 35°C to obtain the composite nanofiber membrane. The highly hydrophilic composite membrane separated a mixed solution of BSA and lysozyme, with a BSA rejection rate >99.4% and a flux recovery rate >93%.
[0027] Example 5 A method for preparing an antifouling composite nanofiber membrane for protein separation, comprising the following specific steps: (1) Preparation of spinning solution: The spinning solution is prepared by the following components according to the mass percentage, wherein PES 80%, PSBMA 20%, total solid content is 20 wt%, and the remainder is dimethyl sulfoxide; PES and PSBMA are dissolved in organic solvent according to the mass percentage, heated and stirred at 60°C for 14 h to form a transparent casting solution, and then allowed to stand to remove bubbles; (2) Electrospinning: The spinning solution was spun under the conditions of 16 kV voltage, 1.2 mL / h feed rate and 16 cm receiving distance to obtain nanofiber base film; (3) Surface activation: The nanofiber substrate obtained in step (2) is immersed in a solution containing 0.3 mol / L trichlorosilane derivative and reacted at 25°C for 2 h to activate and modify the surface of the fiber membrane and introduce initiation sites; (4) Surface grafting polymerization: The activated membrane from step (3) was placed in a reaction system composed of 70% TPMA and 30% CuBr by mass percentage and reacted for 4 h to carry out surface-initiated atom transfer radical polymerization reaction, grafting zwitterionic polymers onto the surface of the nanofiber membrane; after the reaction was completed, the membrane was washed with pure water and dried at 40°C to obtain the composite nanofiber membrane. The SEM image of the surface of the prepared composite nanofiber membrane is shown below. Figure 4 As shown. The highly hydrophilic composite membrane separates a mixed solution of BSA and lysozyme, with a BSA rejection rate >99.5% and a flux recovery rate >90%.
Claims
1. A method for preparing an antifouling composite nanofiber membrane for protein separation, comprising the following specific steps: (1) Preparation of spinning solution: The spinning solution is prepared from the following components in the following mass percentages, wherein, The mixture contains 70-95% hydrophilic polymer, 5-30% zwitterionic polymer, and a total solid content of 10-25 wt%, with the remainder being organic solvent. The hydrophilic polymer and zwitterionic polymer are dissolved in the organic solvent according to their mass percentages, and the mixture is heated and stirred at 60°C for 12-24 h until a transparent casting solution is formed. The solution is then allowed to stand to remove bubbles. (2) Electrospinning: The spinning solution is spun under the conditions of voltage 16-18 kV, feed rate 0.8-1.4 mL / h, and receiving distance 10-16 cm to obtain nanofiber base film; (3) Surface activation: The nanofiber substrate obtained in step (2) is immersed in a solution containing ATRP initiator and reacted at 25°C for 1-3 h to activate and modify the surface of the fiber membrane and introduce initiation sites; (4) Surface grafting polymerization: The activated membrane in step (3) is placed in a reaction system containing ligands and catalysts and reacted for 1-4 h to carry out surface-initiated atom transfer radical polymerization reaction, and zwitterionic polymers are grafted onto the surface of the nanofiber membrane; after the reaction is completed, the membrane is washed with pure water and dried at 30-45℃ to obtain the composite nanofiber membrane.
2. The method according to claim 1, characterized in that, The hydrophilic polymer mentioned in step (1) is one of polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyethersulfone (PES) or polyvinyl alcohol (PVA); the zwitterionic polymer is polysulfobetaine methacrylate (PSBMA) or polycarboxybetaine methacrylate (PCBMA).
3. The method according to claim 1, characterized in that, The organic solvent mentioned in step (1) is one of N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone.
4. The method according to claim 1, characterized in that, The ATRP initiator mentioned in step (3) is 2-bromoisobutyryl bromide (BiBB) or a trichlorosilane derivative initiator.
5. The method according to claim 1, characterized in that, The concentration of the ATRP initiator mentioned in step (3) is 0.1-0.3 mol / L.
6. The method according to claim 1, characterized in that, The ligands mentioned in step (4) are N, N, N', N'', N''-pentamethyldiethylenetriamine (PMDETA) or tris(2-pyridylmethyl)amine (TPMA), and the catalysts are CuCl or CuBr.
7. The method according to claim 1, characterized in that, The reaction system described in step (4) is prepared by mass percentage of 50-70% ligand and 30-50% catalyst.
8. A method for preparing an antifouling composite nanofiber membrane for protein separation according to any one of claims 1-7, wherein the prepared antifouling composite nanofiber membrane is characterized in that, The highly hydrophilic composite membrane separates a mixed solution of BSA and lysozyme, with a BSA rejection rate >99% and a flux recovery rate >90%.